2013
DOI: 10.1002/cne.23395
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal developmental expression of regulator of G protein signaling 14 (RGS14) in the mouse brain

Abstract: Regulator of G Protein Signaling 14 (RGS14) is a multifunctional scaffolding protein that integrates G protein and MAPK signaling pathways. In the adult mouse brain, RGS14 mRNA and protein are found almost exclusively in hippocampal CA2 neurons. We have shown that RGS14 is a natural suppressor of CA2 synaptic plasticity and hippocampal-dependent learning and memory. However, the protein distribution and spatiotemporal expression patterns of RGS14 in mouse brain during postnatal development are unknown. Here, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
103
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(129 citation statements)
references
References 40 publications
18
103
3
Order By: Relevance
“…By contrast, in the absence of G␣ i1 -GDP, RGS14 remains cytosolic yet can be recruited by activated G␣ o -AlF 4 Ϫ to the plasma membrane via the RGS domain. Together with previous observations of RGS14 localization in brain and CA2 neurons (8,9), our findings here suggest that RGS14 exists as distinct cellular subpopulations, either bound to the plasma membrane in complex with G␣ i -GDP or recruited from the cytosol to the plasma membrane by active G␣-GTP followed by capture of the G␣-GDP resulting from GAP activity.…”
Section: Rgs14 Subcellular Localization-our Previous Work Hassupporting
confidence: 88%
See 2 more Smart Citations
“…By contrast, in the absence of G␣ i1 -GDP, RGS14 remains cytosolic yet can be recruited by activated G␣ o -AlF 4 Ϫ to the plasma membrane via the RGS domain. Together with previous observations of RGS14 localization in brain and CA2 neurons (8,9), our findings here suggest that RGS14 exists as distinct cellular subpopulations, either bound to the plasma membrane in complex with G␣ i -GDP or recruited from the cytosol to the plasma membrane by active G␣-GTP followed by capture of the G␣-GDP resulting from GAP activity.…”
Section: Rgs14 Subcellular Localization-our Previous Work Hassupporting
confidence: 88%
“…Our previous studies have indicated that native RGS14 exists both in the soluble (cytosolic) and particulate (membrane) fractions of brain lysates (7), and is localized diffusely within the soma, dendrites, and spines and at the postsynaptic density in CA2 neurons of mouse brain (8,9). We also have shown that recombinant RGS14 can bind inactive G␣ subunits at the plasma membrane through the GPR motif (13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RGS14 is a complex RGS family member that contains a canonical RGS domain, a tandem (R1 and R2) Ras/Rap binding domain (Kiel et al., 2005; Wohlgemuth et al., 2005), as well as a GoLoco/GPR motif. Most prior work on RGS14 focused on its effects on embryonic development and on the visual cortex and central nervous system (Evans, Lee, Smith & Hepler, 2014; Lee et al., 2010; Lopez‐Aranda et al., 2009; Shu, Ramineni & Hepler, 2010; Vellano, Brown, Blumer & Hepler, 2013). The role of BAT in RGS14 KO and its ability to enhance lifespan and improve metabolism, the focus of the present investigation, have never been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the status of RGS2 as an immediate early gene highly expressed in multiple types of neurons throughout the brain allows it to play a unique role in modulating G protein signaling at the synapse. (Cho et al, 2000;Traver et al, 2000;Hollinger et al, 2001) Hippocampus (Traver et al, 2000;Lee et al, 2010;Evans et al, 2014) Somatodendritic compartment of CA2 pyramidal neurons including the PSD (Lee et al, 2010) Suppresses LTP in CA2 hippocampal neurons (Lee et al, 2010;Vellano et al, 2011a) Anxiety (Parker et al, 2012) H-Ras at the R1 Ras binding domain (Willard et al, 2009;Vellano et al, 2013) Piriform cortex (Grafstein-Dunn et al, 2001;Evans et al, 2014) NA Ga i1/3 at the GPR (GoLoco) motif (Hollinger et al, 2001;Kimple et al, 2001;Mittal and Linder, 2004) Orbital cortex (Evans et al, 2014) Striatum ( …”
Section: Rgs Proteins In Synaptic Signaling and Plasticitymentioning
confidence: 99%